EFEKTIVITAS PUPUK HAYATI DAN JENIS PUPUK KANDANG PADA SERAPAN HARA N, P, K DAN PROSES FISIOLOGIS TANAMAN JAGUNG PADA TANAH GAMBUT - Dwi Zulfita; Surachman; Eddy Santoso (AGROISTA : Jurnal Agroteknologi, 2018)
This study aims to examine nutrient uptake of N, P, K and physiological responses of maize plants on peat soil due to the treatment of biological fertilizers and types of manure and to find out the interaction between biological fertilizers and types of manure on N, P, K absorption and physiological responses of maize plants peat. The research was carried out at a location located in Rasau Jaya 2 Village, Rasau Jaya District. The study took place from April 4 to August 14, 2018. Research with field experiments was carried out with a 2 x 3 randomized group (RCBD) factorial treatment design with 3 groups. Biological fertilizer factor (M) consists of 2 levels, namely m0 (without biological fertilizer), and m1 (with biological fertilizer). Type of Manure Fertilizer (P) consists of 3 levels, namely p1 (Chicken Manure), p2 (goat manure) and p3 (Cow Manure). Observations were made on root infections, and nutrient uptake N, P, K. Observations on the analysis of plant growth included Leaf Area Index, Net Assimilation Rate and Plant Growth Rate. Data from the observations were analyzed statistically using analysis of variance (F test). Advanced tests using Duncan's multiple range test (DMRT). The results showed that nutrient uptake of N, P, K and physiological processes of maize plants fed with biofertilizer were better than maize plants without biofertilization, the provision of chicken manure resulted in the best nutrient uptake of N, P, K and physiological processes of maize plants compared to goat manure and cow manure fertilizer, giving biofertilizers to all types of manure (chicken manure, goat manure, and cow manure) can increase nutrient uptake of N, P, K and maize physiologis process on peat soil. Keywords : Biofertilizer, manure, nutrient uptake N, P, K, physiological process